Haematological and renal biochemistry values in white-tailed deer (Odocoileus virginianus peruvianus) reared in captivity - Lovera P., Erick (2011)
The objective of the present study was to determine the normal hematological values and renal biochemistry of the adult white-tailed deer (Odocoileus virginianus) reared in captivity. Blood samples were collected in 25 animals. The deers were anesthetized with two chemical methods of restraint (ketamina 7 mg/kg; ketamina 4 mg/kg and xilacina 1 mg/ kg) without significant difference between both methods in relation to hematological and biochemistry values. In the erythrocytic series, the number of red cells was 10.12 x 106/μl, hemoglobin was 9.5 g/dl, hematocrit was 28.9%, and the erythocytic indexes were VCM = 28.8 fL, HCM = 9.6 pg, CHCM = 33.2 g/dl, without differences due to sex. The number of leukocytes was statistical different (p<0.05) between females (4018 x 103/μl) and males (3059 x 103/μl), but the differential count was similar between sexes (neutrophils: 55.5%, lymphocytes: 39.8%, monocytes: 0.1%, eosinophils: 4.6%). In the renal biochemistry, the mean values for urea and creatinine were 47 mg/dl and 2.1 mg/dl respectively.